Optimal sizing of stand alone photovoltaic stations - 446342 Megat Hazlan Megat Hashim (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2003